RETRACTION Sutapa , P.., Pratama, K. W., & Mustapha, A. (2024). La relación entre el nivel de aptitud física y el nivel de depresión en la vejez según el sexo y el estado civil (The relationship between the level of physical fitness and the level of depression in elderly age based on gender and marital status). Retos, 53, 36–44. https://doi.org/10.47197/retos.v53.102488 - RETOS, RETOS (Retos, 2025)
Sutapa , P.., Pratama, K. W., & Mustapha, A. (2024). La relación entre el nivel de aptitud física y el nivel de depresión en la vejez según el sexo y el estado civil (The relationship between the level of physical fitness and the level of depression in elderly age based on gender and marital status). Retos, 53, 36–44. https://doi.org/10.47197/retos.v53.102488Retraction of the article by the editor of the journal. There has been several clear and conclusive proofs that there has been a manipulation of the authorship of the article. The accepted Word document was sent with the names of the authors that appeared in the “Corrections for the edition” message so that they could only make the orthographical corrections that were necessary. The corresponding author (or whoever hurt him) changed the authors of the aforementioned Word document that was sent to them, returning a document together with these corrections made with new authors, all without any express notification, without any document explaining the changes made accepted by all the authors and, of course, without express authorization from the journal Retos between both moments. With this fraudulent document the galleys were made and the article was definitively published, assigning it the corresponding DOI.Authors in the Word document of the article submitted for review: 7Authors in the published PDF with modified authors: 8Differences between the authors between both moments: +1 (Kukuh Wahyudin Pratama)